THE DIFFERENCE OF EFFECTIVENESS BETWEEN PRACTICE THERAPY OF WILIAM’S FLEXION WITH PRACTICE THERAPY OF MCKENZIE EXTENSION AT PATIENT WITH POSTURAL LOW BACK PAIN - Wahyuni, Nila (Majalah Ilmiah Fisioterapi Indonesia; Vol 1 No 2 (2013): Majalah Ilmiah Fisioterapi Indonesia, 2013)
This Research aim to to know effectiveness practice therapy of William's Flexion to increase lumbosacral range of motion at patient with postural low back pain, to know effectiveness practice therapy of Mc Kenzie Ekstension to increase lumbosacral range of motion at patient with postural low back pain and to know difference of effectiveness practice therapy of William's Flexion with practice therapy of Mc Kenzie ekstension to increase lumbosacral range of motion at patient with postural low back pain. Researcher was done this research at any practice physiotherapy private in Denpasar, in December 2011-February 2012. Sampel amount to 24 people who is taken at random. Method research is eksperimental with pre test post and test group design. Group I was given therapy of SWD and practice therapy of Williams Fleksion and group of II was given therapy of SWD and practice therapy of Mc Kenzie Ekstension. Measurement of increasing of move joint use schober test and the equipment that was used is flexible curve. All sampel in group I and group II show positive result which are increase lumbosacral range of motion after was given treatment. Data processing and analyse the data processed use Statistical Program for Social Science (SPSS). Hypothesis I and II analyze with Wilcoxon Signed Ranks Test. Result of test show movement of fleksion and also ekstensi is valuable ( p<0,05), so we can concluded that there are significan influence of SWD therapy and practice therapy of William Flexion and Mc Kenzie Ekstension to increase lumbosacral range of motion at patient with postural low back pain. Hypothesis III is comparison increasing lumbosacral range of motion between treatment of SWD and practice therapy of William Fleksion with SWD and practice therapy of Mc Kenzie Ekstension analyze with Mann Whitney Test. Result of test show there is no siginifican difference between practice therapy of Williams Flexion with Mc Kenzie Ekstension, that is shown with result for the fleksion movement p = 0,930 ( p>0,05) and for the ekstension movement p = 0,651 ( p>0,05). Average value show that is treatment of William Flexion at fleksion movement is 12,38, and ekstension movement is 13,13. While at treatment of Mc Kenzie Ekstension at fleksion movement is 12,63 and ekstension movement is 11,88.
Keywords: Practice therapy of Williams Fleksion, practice therapy of Mc Kenzie Ekstension, SWD, range of motion.